Efektivitas Penerapan Kebijakan Pajak Pertambahan Nilai atas Perdagangan Melalui Sistem Elektronik (PMSE) dalam Peningkatan Penerimaan Pajak di KPP Badan dan Orang Asing (BADORA) Tahun - Sinta Sania; Rahadi Pramono Singgih; Supriyono (Jurnal Ilmu Administrasi Publik, 2025)
This study aimed to analyze the effectiveness of implementing the Value-Added Tax (VAT) policy on Electronic Commerce (EC) in increasing tax revenue at the Tax Office for Legal Entities and Foreign Individuals (BADORA) in 2024. The background of this study is the increasing number of digital transactions that are not yet fully covered by the tax system. The approach used is descriptive qualitative. Data was obtained through interviews with tax officials, consultants, and academics. Analysis used Riant Nugroho's policy effectiveness theory with five indicators: policy accuracy, implementers, targets, environment, and process. The results indicated that the PPN PMSE policy is sufficiently effective in increasing tax revenue. Effectiveness is supported by a digital reporting system, business compliance, and inter-agency support. However, challenges remain, such as insufficient business understanding and cross-border reporting challenges.